IRF5 and IRF8 modulate the CAL‐1 human plasmacytoid dendritic cell line response following TLR9 ligation. Issue 3 (17th December 2015) - Steinhagen, Folkert; Rodriguez, Luis G.; Tross, Debra; Tewary, Poonam; Bode, Christian; Klinman, Dennis M.
Abstract : Synthetic oligonucleotides (ODNs) containing CpG motifs stimulate human plasmacytoid dendritic cells (pDCs) to produce type‐1 interferons (IFNs) and proinflammatory cytokines. Previous studies demonstrated that interferon regulatory factors (IRFs) play a central role in mediating CpG‐induced pDC activation. This work explores the inverse effects of IRF5 and IRF8 (also known as IFN consensus sequence‐binding protein) on CpG‐dependent gene expression in the human CAL‐1 pDC cell line. This cell line shares many of the phenotypic and functional properties of freshly isolated human pDCs. Results from RNA interference and microarray studies indicate that IRF5 upregulates TLR9‐driven gene expression whereas IRF8 downregulates the same genes. Several findings support the conclusion that IRF8 inhibits TLR9‐dependent gene expression by directly blocking the activity of IRF5. First, the inhibitory activity of IRF8 is only observed when IRF5 is present. Second, proximity ligation analysis shows that IRF8 and IRF5 colocalize within the cytoplasm of resting human pDCs and cotranslocate to the nucleus after CpG stimulation. Taken together, these findings suggest that IRF5 and IRF8, two transcription factors with opposing functions, control TLR9 signaling in human pDCs.